LEGAL TRANSFORMATION OF MOVABLE WAQF: Contemporary Legal and Regulatory Perspectives in Modern Indonesia - Tajhi, Ahmad Irham; Warman, Syafril; Arif, Zuhri (UIN Sumatera Utara, 2025)
This article discusses the legal transformation of movable waqf in the context of current laws and regulations in Indonesia, particularly in the modern era. Waqf, which is commonly known in the form of land and fixed property, has experienced developments in terms of the objects that can be waqfed, including movable objects such as money, vehicles, and other equipment. This study outlines the changes in legal perspectives that have occurred in line with the development of regulations and policies related to the waqf of movable objects, including Law No. 41/2004 on Waqf, as well as its implementing regulations. In addition, the article also highlights the challenges and opportunities that arise in the implementation of movable waqf in Indonesia, as well as the role of religious institutions and the government in regulating and ensuring the sustainability of movable waqf. Hopefully, this article can provide a deeper understanding of the potential and legal implications of movable waqf in Indonesia's increasingly dynamic legal system.Keywords: Legal Transformation, Waqf Legislation, Contemporary Waqf, Utilization of Movable Assets